Determination of Queercetin Content in Preparation of Powder Extract of Starfruit Leaves (Averrhoa bilimbi L.) by Tlc-Densitometry - Sudjarwo, Sudjarwo; Zulfiyah Emaz; Amirudin Prawita (Universitas Airlangga, 2023)
Quercetin was a flavonoid from Averrhoa bilimbi Linn. which had a variety of potential therapeutic uses. Therefore, this research was needed to determine the quercetin content in Averrhoa bilimbi L.’s extract powder. Method validation was performed to ensure that an analytical method met the criteria and requirements of a good analysis method. Method validation used was the first category with parameters of selectivity, linearity, accuracy, and precision. The content of quercetin in Averrhoa bilimbi L.’s leaf was small, which required the parameters of Limit of Detection (LOD) and Limit of Quantitation (LOQ). The analysis method was by TLC-Densitometry with Silica gel 60 F254, eluent of toluene: ethyl acetate: formic acid (7:3:1) as the mobile phase with a resolution of 1,67 and 1,60, respectively. The results showed a linear regression of y = 8122,4899 x + 1181,9943 (r: 0,9976; Vxo 4,88%). The accuracy was 90,2% (w/w) ± 5,89; the coefficient of variation of precision was 1,35%; LOD and LOQ were 0,0064 µg, and 0,0215 µg, respectively. The determination result showed that quercetin content in the leaf extract in ethanol of Averrhoa bilimbi L. was 0,58% (w/w) ± 0,04, and the determination of quercetin from 4,0 g extract powder of Averrhoa bilimbi L. leaf showed that the average content of quercetin was 6,05 ± 0,09 mg. Keywords: Quercetin, Extract Powder, Averrhoa bilimbi L, TLC-Densitometry